Analysis of Sexual Knowledge towards Sexual Behavior Patterns among Adolescents in Medan Tuntungan District - Putri Gea Maba Rizky; Yusnadi; Muhammad Takwin Machmud (PT. Global Research Collaboration, 2024)
This study was conducted with a qualitative approach aimed at understanding individual perspectives, identifying and describing processes, and exploring limited research topics or backgrounds with detailed information. The background of this topic selection is to measure the level of sexual knowledge of adolescents in Medan, analyze their behavior patterns, and analyze the relationship of sexual behavior with the level of sexual knowledge of adolescents. This study used a type of qualitative research that was descriptive. The study subjects used in this study were all adolescents in Tuntungan Medan. Researchers choose purposive sampling methods when selecting research subjects. The data collection techniques used in this study was the spread of questionnaires and the data collection tools used were questionnaires or questions. Research results show that some teens are already pregnant with sexual knowledge, but some teens lack sufficient knowledge. The consequence of this is that adolescents can commit reckless sexual behavior, such as premarital sex with their spouses. Therefore, it is important to provide comprehensive sex education to adolescents, covering aspects such as body anatomy, reproductive health, and sexual knowledge. In addition, adolescents have access to accurate and reliable information about sex through school education, access to reliable information sources, and open communication between adolescents and their parents.